Nuts and bolts of PMMC flap in oral cancer and its clinical outcome in 168 indian patients: A retrospective analysis - Vijaykumar Girhe; Akanksha A. Auti; Prachi Girhe; Rohinee Wagre (Elsevier, 2021)
Introduction: The gold standard for reconstruction is the microvascular free flaps, whereas pedicled flaps are generally employed as a rescue procedure. Pectoralis major myocutaneous flap (PMMC) flap being a reliable flap is associated with high rate of complication. So, the purpose of this study was to check and assess the predictability of PMMC Flap and its clinical outcome in 168 Indian patients. Materials and method: We conducted a retrospective study of PMMC flap which was harvested in 168 Indian oral cancer patients in 3 years time span. Patients were kept on follow up for 1-3 years. Rate of complication were documented for flap necrosis and wound dehiscence; and patient related data like neck bulk acceptance and range of motion were recorded. Gender comparison of complications were also documented. Results: The most common complication was wound dehiscence in 11 (6.5%) patients. Partial flap necrosis was observed in 3 (1.8%) female patients. There was no case of total flap necrosis. Questionare method was used for patients to record neck bulk acceptance. Range of motion was evaluated during follow up period. Follow up period of all the patients was 1-3 years. Conclusion: PMMC flap is still a well founded 'workhorse' flap for reconstruction in head and neck cancer patients and can be used successfully with acceptable morbidity.